TOWARDS AN APPROPRIATE EFFORT-BASED FISHERY MODEL FOR THE TUNA FISHERY OF MALDIVES - Kumar, R Sathiendra; Tisdell, C A (Indian Journal of Fisheries, 2011)
This paper considers the applicability of the Schaefer model and the Foxmodel to the tuna fishing industry of the Maldives. Examinaition of Maldiviaocatch apd effort data throws doubt upon the applicability of these models to thisfishing industry, which depends on a highly migratory species. An alternative production-type model based on a population threshold assumption is suggested andfound to be much more consistent with Maldivian effort and catch data. Such amodel may also have application to some other fisheries based on migratoryspecies.